2000
DOI: 10.1111/j.1348-0421.2000.tb02494.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of Membrane Vesicles Containing Endotoxic Lipopolysaccharide in Escherichia coli O157:H7 Clinical Isolates

Abstract: Membrane vesicles released by E. coli 0157:H7 strains were investigated by immuno-electron microscopy using anti-0157 antibody. Anti-0157 antibody enhanced the negative-staining of vesicles and we found numerous small vesicles clearly formed around bacterial cells. An immunogold-electron microscopic examination confirmed that lipopolysaccharide (LPS) including the O-side chain is present on the surface of the vesicles. Sodium dodecyl sulfate polyacrylamide gel electrophoresis analysis of the purified vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…This work demonstrated that both Stx1 and Stx2 are released, at least in part, as the MV-associated fraction from all 46 STEC strains under aerobic and anaerobic conditions. These results are consistent with previous observations that STEC O157 releases MVs [22] and that these MVs export virulence genes and Stx as measured with mixed antibodies [17]. We thus conclude that the release of Stx1 and Stx2 by MVs is a general delivery mechanism in STEC.…”
Section: Discussionsupporting
confidence: 82%
“…This work demonstrated that both Stx1 and Stx2 are released, at least in part, as the MV-associated fraction from all 46 STEC strains under aerobic and anaerobic conditions. These results are consistent with previous observations that STEC O157 releases MVs [22] and that these MVs export virulence genes and Stx as measured with mixed antibodies [17]. We thus conclude that the release of Stx1 and Stx2 by MVs is a general delivery mechanism in STEC.…”
Section: Discussionsupporting
confidence: 82%
“…In some cases, these vesicles have been related to the transport of pathogenic factors. Examples include the VacA toxin of H. pylori (Keenan et al, 2000), Shiga toxin and lipopolysaccharide by STEC (Shiga-toxin producing E. coli) and EHEC (Wai et al, 1995 ;Meno et al, 2000 ;Yokoyama et al, 2000). In other cases outermembrane vesicles have been shown to contain muramidases and other periplasmic enzymes (Kadurugamuwa & Beveridge, 1995, 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Hence the formation of vesicles, which act as vehicles for carrying toxins, is thought to be an important virulence factor for these pathogens including STEC. Recently, a few studies reported that E. coli O157:H7 strains release Stx1, virulence genes of eae, stx1 and stx2 and endotoxic lipopolysaccharide via vesicles (4,6 In this study, we performed morphological detection of antimicrobial-induced vesicles in Shigella dysenteriae type 1 using electron microscopy and determined the release of Shiga toxin by the organism via vesicles. The present study also demonstrates the effects of most commonly used antimicrobials on in vitro Shiga toxin production and release by S. dysenteriae type 1 strain.…”
mentioning
confidence: 99%
“…Toxin titre was determined in ruptured bacterial cell suspension after centrifugation. The vesicles were isolated from the bacterial culture supernatant by the method reported by Meno et al with some modification (6). The supernatant was passed through cellulose acetate membrane (0.45 µm pore size) and filtrate was ultracentrifuged (Hitachi centrifuge, Japan, model SCP70 HT with rotor RP70T) at 90,000ϫg for 1 hr at 4 C. The pellet comprising crude vesicles deposited at the bottom was suspended in 200 µl of PBS, the suspension was treated with polymyxin B (5,000 U/ml) for 1 hr at 37 C and toxin titre was measured in ruptured vesicles after centrifugation.…”
mentioning
confidence: 99%